1997
DOI: 10.1002/(sici)1096-8628(19970414)69:4<360::aid-ajmg5>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Constitutional mosaicism for a chromosome 9 inversion resulting in recombinant aneusomy in an offspring

Abstract: We report on a case of constitutional mosaicism for a large pericentric inversion of chromosome 9 in a man whose daughter had recombinant aneusomy resulting in partial 9q duplication and partial 9p deletion. At age 6 months, the girl was evaluated because of congenital anomalies [corrected] and developmental delay. Chromosomal analysis on this infant showed a derivative chromosome 9 which was later determined to be a recombinant chromosome with trisomy of 9q34.1-->qter and monosomy of pter-->9p24. Chromosomal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
2
6
0
Order By: Relevance
“…Since reproductive failure affects about 15 % of couples, one may calculate population rates of N/rcp, N/inv, N/unbal Rea as 0.02 ‰, 0.005 ‰, and 0.002 ‰, respectively. Therefore, population rates for balanced Reas calculated in the present study, are consistent with figures from prenatal samples [ 22 ]. However, it should be noted that these figures are most probably underestimated since in many cases mosaicism goes undetected because of the presence of normal cell line.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Since reproductive failure affects about 15 % of couples, one may calculate population rates of N/rcp, N/inv, N/unbal Rea as 0.02 ‰, 0.005 ‰, and 0.002 ‰, respectively. Therefore, population rates for balanced Reas calculated in the present study, are consistent with figures from prenatal samples [ 22 ]. However, it should be noted that these figures are most probably underestimated since in many cases mosaicism goes undetected because of the presence of normal cell line.…”
Section: Resultssupporting
confidence: 88%
“…Reviewing data from prenatal amniocentesis samples, Shapira et al [ 22 ] reported the rates of mosaic balanced reciprocal translocations as <0.02–0.1 per 1,000 samples and suggested that these rates may approximate the true frequency in the general population. However, mosaicism detected in amniocytes might not be confirmed in blood cells postnatally.…”
Section: Resultsmentioning
confidence: 99%
“…Besides BRT, mosaicism for other structural rearrangement such as inversion has also been reported [Shapira et al, 1997]. Unlike mosaicism for numerical abnormalities in which the error can be meiotic [Pangalos et al, 1994], the abnormal cell line in mosaicism for a structural rearrangement always results from a postzygotic mitotic error.…”
Section: Discussionmentioning
confidence: 99%
“…In 2007, one of the responsible gene for trigonocephaly, CD96 , was identified on chromosome 3 [Kaname et al, 2007]. Further case reports suggest the next candidate region may involve 9p24.1, that is, a patient having a cryptic chromosomal deletion in 9p24.1p23 derived from paternal 3;9 translocation [Wagstaff and Hemann, 1995], a case of inv(9)(p24q34.1) [Shapira et al, 1997], and six cases of der(9)t(9;19)(p24.1;q13.4) [Su et al, 2005]. Molecular investigation identified the next critical region of trigonocephaly, which has been confined to an 8‐Mb interval between two microsatellite markers, D9S286 and D9S285, by the genotype–phenotype comparison (Fig.…”
Section: To the Editormentioning
confidence: 99%